Selection criterio of Beauveria bassiana isolates for the control of the coffee berry borer Hypothenemus hampei - VARELA-RAMÍREZ, AMANDA (Revista Colombiana de Entomología, 1997)
Six isolates of the entomopathogens fungus Beauveria bassiana were selected from the culture collection of the Laboratorio de Investigaciones Sobre la Química del Café y sus Productos Naturales (LIQC). The purpose of this study was to examine some of the macroscopic, microscopic, physiological y biochemical characteristics of these isolates, in order to establish which ores of these could be used for differentiation of isolates. Moreover, these characters were analyzed for their relationship with the virulence of isolates against Hypothenemus hampei. The macroscopic characteristics of the colon íes such a color. type, aspect, stemmata, and oosporein production, could not be used for isolates differentiation, because they are so variable. The microscopic characteristics evaluated, neither the size and from of the conidia nor the relative abundance of blastoconidia, could be utilized to differentiate the isolates. The conidial resistance to high temperatures and conidial resistance to their exposition to ultraviolet light and the lipase production were the only characters that differentiated isolates. However, these physiological features only classified the isolates in groups and they do not allow their differentiation individually. The banding patterns of a- y 13-esterases were clearly distinctive for each isolate, with unique bands, except the 8906 isolates (origin from Cuba). It was not found the existence of any type of relationship between the characteristics evaluated in this study, nor between these characters and the virulence of isolates against the coffee berry borer. However, based on the results of this study it can be suggested that the isolates 8505 and 8905, maybe in a mixture. could be used in biological control programs. The reason for this suggestion is that these isolates have a group of important biological features, Any case. before to use these isolates, its behaviour under field conditions might be evaluated.